2020
DOI: 10.1007/s41999-020-00376-1
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy, benzodiazepines, and antidepressants, but not antipsychotics, are associated with increased falls risk in UK care home residents: a prospective multi-centre study

Abstract: Aim To explore the link between polypharmacy, psychotropic medications, and falls risk in a cohort of UK care home residents. Findings Polypharmacy and psychotropic drugs are predictive of falls in UK care home residents. Message Deprescribing interventions relating to psychotropic drugs should continue to be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
(28 reference statements)
2
22
0
Order By: Relevance
“…In the present study, we defined the time of enrollment as the start of follow up; therefore 30‐day follow up was very short term, and patients might still be very careful to adhere to the discharge education program, such as falls prevention and a healthy lifestyle. However, regarding the long‐term follow up, we found that older inpatients with polypharmacy had a higher risk of 90‐day falls (OR 1.73, 95%CI 1.04, 2.80) and 1‐year falls (OR 1.44, 95% CI 1.03–2.02), which was in line with other previous studies 11,15 . In a 2020 study of nursing home residents, polypharmacy was a stronger risk factor of falls; with the greater number of medications, the higher risk of falling 15 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the present study, we defined the time of enrollment as the start of follow up; therefore 30‐day follow up was very short term, and patients might still be very careful to adhere to the discharge education program, such as falls prevention and a healthy lifestyle. However, regarding the long‐term follow up, we found that older inpatients with polypharmacy had a higher risk of 90‐day falls (OR 1.73, 95%CI 1.04, 2.80) and 1‐year falls (OR 1.44, 95% CI 1.03–2.02), which was in line with other previous studies 11,15 . In a 2020 study of nursing home residents, polypharmacy was a stronger risk factor of falls; with the greater number of medications, the higher risk of falling 15 .…”
Section: Discussionsupporting
confidence: 89%
“…However, regarding the long‐term follow up, we found that older inpatients with polypharmacy had a higher risk of 90‐day falls (OR 1.73, 95%CI 1.04, 2.80) and 1‐year falls (OR 1.44, 95% CI 1.03–2.02), which was in line with other previous studies 11,15 . In a 2020 study of nursing home residents, polypharmacy was a stronger risk factor of falls; with the greater number of medications, the higher risk of falling 15 . This association was also supported by a study of Dhalwani et al .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In another study, the number of fall-risk medications was associated with fall-related hospital admissions though polypharmacy could not be identified as an independent risk factor [ 79 ]. Recently, a prospective cohort study also revealed that polypharmacy is associated with an increased falls risk in UK care home residents [ 80 ].…”
Section: Search Strategymentioning
confidence: 99%